Inter-Stage Output Voltage Amplitude Improvement Circuit Integrated with Class-B Transmit Voltage Amplifier for Mobile Ultrasound Machines - You, Kiheum (Sensors (Basel), 2020)
Piezoelectric transducers are triggered by the output voltage signal of a transmit voltage amplifier (TVA). In mobile ultrasound instruments, the sensitivity of piezoelectric transducers is a critical parameter under limited power supply from portable batteries. Therefore, the enhancement of the output voltage amplitude of the amplifier under limited power supply could increase the sensitivity of the piezoelectric transducer. Several-stage TVAs are used to increase the voltage amplitude. However, inter-stage design issues between each TVA block may reduce the voltage amplitude and bandwidth because the electronic components of the amplifier are nonlinearly operated at the desired frequency ranges. To compensate for this effect, we propose a novel inter-stage output voltage amplitude improvement (OVAI) circuit integrated with a class-B TVA circuit. We performed fundamental A-mode pulse-echo tests using a 15-MHz immersion-type piezoelectric transducer to verify the design. The echo amplitude and bandwidth when using an inter-stage OVAI circuit integrated with a class-B TVA circuit (696 mV(PP) and 29.91%, respectively) were higher than those obtained when using only the class-B TVA circuit (576 mV(PP) and 24.21%, respectively). Therefore, the proposed OVAI circuit could be beneficial for increasing the output amplitude of the class-B TVA circuit for mobile ultrasound machines.